KETERSEDIAAN PANGAN POKOK PADA RUMAH TANGGA PETANI PADI SAWAH IRIGASI DAN TADAH HUJAN DI KABUPATEN KARANGANYAR - Wiwit Rahayu (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2014)
This study aims to determine the supply pattern of staple food , the  availability of staple food, and energy  avaibility from staple foods on the irrigated and rainfed rice farmers household in Karanganyar Regency. Samples totaling 150 rice farming households consisting of 90 irrigated rice farmers households and 60 rainfed rice farmers households  in four districts ( Karanganyar, Gondangrejo, Jaten, and Jatipuro District ) in the Karanganyar  Regency. Data used include the primary and secondary data. Data were analyzed descriptively. The results showed that the supply pattern  of staple food on rice farmer households in Karanganyar is from  production itself  and production itself plus of purchase. Average of staple food avaibility on irrigated rice farmer household  was 64.75 Kg per month and 65.05 kg per month on rainfed rice farmers  household. Average availability of energy from staple food on irrigated rice farmers household  was  2516.69 kcal / person / day and on the rainfed rice farmer households    was3584.53kcal/person/day.Keywords: Availability, staple food, energy, Karanganyar Regency